Scientific recognition in numbers: analysis of the profile of a vanguard from Lattes curricula vitae - Miguel Ângelo Montagner; Maria Inez Montagner; Eduardo Luiz Hoehne (Faculdade de Medicina de Botucatu (Unesp), 2010)
The objective was to analyze the possibilities and limitations of quantitative study on an institution and its professionals, taking into account the Lattes curriculum vitae platform. Through exploring this material, we sought to delineate the profile of professors of the UNICAMP School of Medical Sciences and to characterize their scientific production, main activities and academic profile. The methodology used was quantitative. Based on descriptive statistics, we outlined and analyzed the main characteristics these professors presented in their curricula vitae, which are stored in the database of the Lattes Platform. Next, using qualitative analysis based on the theories of Pierre Bourdieu, we emphasized the difficulties in achieving good descriptions of researchers' social and scientific paths based on the Lattes Platform. Thus, the Lattes system consists of a repository of finished scientific actions, comprising a linear, non-historical succession within official science.